2021
DOI: 10.1017/s0022215121002036
|View full text |Cite
|
Sign up to set email alerts
|

Parotid incidentalomas: a systematic review

Abstract: Objective Parotid incidentalomas on fluorodeoxyglucose positron emission tomography/computed tomography imaging are rare. A systematic review was performed to assess their aetiology and association with scanning indication, and to develop an evidence-based algorithm for their management. Methods A literature search was performed on 25 August 2020 using the keywords ‘incidentaloma’, ‘incidental finding’, ‘parotid’, ‘parotid gland’, ‘salivary gland’ and ‘head and neck’. Articles were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…According to a recent systematic review, the overall prevalence of PIL in various primary tumor staging examinations using 18 F-FDG PET/CT was 0.74%, with a significantly higher frequency observed in patients with lung cancer [ 16 ]. In our study, PIL was detected in 2.7% of patients with HCC, showing a higher prevalence compared with other non-head and neck primary cancers, and a higher likelihood of detection in patients with head and neck cancer (2.1%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent systematic review, the overall prevalence of PIL in various primary tumor staging examinations using 18 F-FDG PET/CT was 0.74%, with a significantly higher frequency observed in patients with lung cancer [ 16 ]. In our study, PIL was detected in 2.7% of patients with HCC, showing a higher prevalence compared with other non-head and neck primary cancers, and a higher likelihood of detection in patients with head and neck cancer (2.1%) [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the aforementioned systematic review by Thompson and colleagues, the majority of tumors found in cases wherein histological confirmation was available were benign, such as Warthin tumor (cystadenoma). However, malignant lesions were identified in approximately 30% of cases, including metastatic LNs and primary parotid gland malignancies [ 16 ]. In contrast, among the 54 patients in our study who underwent histological confirmation for PIL, no malignant lesions were found.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of thyroid nodules continues to present significant challenges for treating physicians. The frequent use of high-resolution ultrasound (US) in conjunction with carotid Doppler techniques revealed the existence of an increasing number of incidentalomas or asymptomatic thyroid nodules [ 4 ]. The sensitivity of the US is high for identifying the nodules, and the US characteristics of the nodules can help determine whether further investigation is required [ 5 ].…”
Section: Introductionmentioning
confidence: 99%